A Comparative Study Between The Views Of Imam Al-Ghazali And Imam Al-Zarnuji On The Student’s Etiquette Towards The Teacher - Qoidy Hilman Hindami; Mohammad Asrori; Abdul Aziz (al-Afkar, Journal For Islamic Studies, 2025)
Imam Al-Ghazali and Imam Az-Zarnuji are religious scientists who are very concerned about the world of education, especially in terms of Student etiquette towards Teachers. the purpose of this study is to determine the views of Imam Al-Ghazali and Imam Az-Zarnuji in terms of Student etiquette towards Teachers, as well as to find out the similarities and differences from the views of both. This research uses a descriptive qualitative research method with a library research approach, which focuses on a series of studies related to library data collection methods or research conducted in libraries. The method of content analysis, namely the data obtained is textual descriptive data. the results of this study show a summary of Imam Al-Ghazali thoughts and a summary of Imam Az-Zarnuji thoughts about Student etiquette towards Teachers In addition, this study also shows the similarities and differences between the views of Imam Az-Zarnuji and Imam Al-Ghozali about Student etiquette towards Teachers.